2011
DOI: 10.1152/ajpcell.00257.2011
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor regulation of neural chemorepellent Sema3A expression in satellite cell cultures

Abstract: Successful regeneration and remodeling of the intramuscular motoneuron network and neuromuscular connections are critical for restoring skeletal muscle function and physiological properties. The regulatory signals of such coordination remain unclear, although axon-guidance molecules may be involved. Recently, satellite cells, resident myogenic stem cells positioned beneath the basal lamina and at high density at the myoneural junction regions of mature fibers, were shown to upregulate a secreted neural chemore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…joint contracture and muscle weakness observed in the patient might well be explained by Sema3a deficiency [Huber et al, 2005;Do et al, 2011].…”
Section: Discussionmentioning
confidence: 76%
“…joint contracture and muscle weakness observed in the patient might well be explained by Sema3a deficiency [Huber et al, 2005;Do et al, 2011].…”
Section: Discussionmentioning
confidence: 76%
“…1 of Do et al 2012). Considering that the dose-dependent up-regulation of Sema3A by HGF has a maximum at 10-25 ng/mL HGF in primary cultures of early-differentiated satellite cells (Tatsumi et al 2009;Do et al 2011), additional local sources of HGF production may be required during the earlydifferentiation phase in vivo, in order to regulate differentiation and moto-neuritogenesis; this positions the population of M2 macrophages into being a highly plausible candidate. M2 macrophages are prevalent at precisely the cell stage of differentiation and have greater ability to produce and secrete large amounts of HGF (Sakaguchi et al, in press) compared to M1 macrophages and satellite cells, therefore advancing our understanding of the spatiotemporal contribution of M2 cells to regenerative moto-neuritogenesis including a coordinated delay in attachment of motoneuron terminals onto damaged and generated muscle fibers early in muscle regeneration in synchrony with recovery of muscle-fiber integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that satellite cells, resident myogenic stem cells normally found at high density at the neuromuscular junction regions of mature fibers (Kelly 1978;Wokke et al 1989;Bischoff & Franzini-Armstrong 2004), up-regulate a secreted neural chemorepellent semaphorin 3A (Sema3A), during the earlydifferentiation period following in vivo muscle injury by crush or cardiotoxin (CTX)-injection (Tatsumi et al 2009;Sato et al 2013). Importantly, hepatocyte growth factor (HGF) triggered its expression exclusively at the early-differentiation phase in primary satellite-cell cultures and in satellite cells resident on muscle fibers (Tatsumi et al 2009;Do et al 2011;Suzuki et al 2013) and the effect of HGF was prevented by co-addition of transforming growth factor (TGF)-β2 and 3 (Do et al 2011). The physiological significance of these manipulations was ensured by in vivo time-course experiments of growth factor concentrations in extracellular wound fluids that showed that active HGF is prevalent 4-6 days after crush-injury of rat Gastrocnemius muscle, whereas TGF-β3 increases at 12-14 days (Do et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both effects were prevented by adding transforming growth factor (TGF)- β 2, 3 in culture (Do et al. 2011). Similarly, in cultures of the mouse C2C12 myoblasts, Sema3A secretion was upregulated 2 days after switching to differentiation media and returned to baseline 3 days later (Henningsen et al.…”
Section: Introductionmentioning
confidence: 99%
“…1A, B and 2 in Do et al. 2011), both growth factors may share a common binding/signaling receptor(s), although a receptor using protein–protein interactions for ligand binding is unlikely since HGF and FGF2 proteins do not have significant sequence homology. This idea is supported by our previous observation that tyrosine kinase c-met, a specific receptor for HGF, was excluded as mediating this signaling pathway, since treatment with anti-c-met neutralizing antibody did not affect HGF-induced Sema3A upregulation (see Fig.…”
Section: Introductionmentioning
confidence: 99%